'walking Backwards into Tomorrow' Historical Consciousness and Understanding History. Issue 1 (1st January 2004) - Lee, Peter
Abstract : This paper, which should be viewed as work in progress rather than as a research report or a finished conceptual argument, examines some elements of Jörn Rüsen's theory of history and historical consciousness. It makes a preliminary and tentative attempt to tease out the ways in which Rüsen's theory may be helpful or problematic for thinking about history education's role in orienting young people in time, and in particular the extent to which his typology of the ontogeny of historical consciousness may be useful for researchers; It is suggested that any theory of historical consciousness and its development in students should pay attention to students' metahistorical understanding — of the discipline of history — as well as their conceptions of the past. A strength of Rüsen's theory of historical consciousness is that it demands attention to both these two kinds of ideas, and points up the relationships that must exist between them. However, the ontogenetic typology offered by Rüsen needs to be treated with care by researchers. This is because its very attempt to provide an all-encompassing account of the development of historical consciousness, whether or not it is seen as exhaustive, compels it to conflate matters that demand differentiated analysis. Rüsen himself recognizes that the development of historical consciousness is an empirical matter, and a consequence of this stance is that whether or not ideas develop together or are decoupled is for research to determine, and that there are many ways of conceptualizing the basis upon which such ideas may be grouped. As with history, these will depend on the questions researchers are asking; It is argued that Rüsen's account of history and historical consciousness gives us strong reasons to think more carefully about the kind of past available for students for purposes of orientation. Rüsen emphasizes the importance of existing narratives, which must be taken seriously in history education, but the focus of this paper is on the possibility of open frameworks of the past that allow students to generate alternative narratives in response to their questions and interests. It is suggested that such frameworks demand powerful metahistorical ideas about the nature of the discipline of history if they are to allow the kind of orientation that Rüsen requires; Finally, some very early exploratory research is discussed, not because it can 'show' anything at all, but because it suggests directions for research that can profitably pay attention to Rüsen's theory. Among these are questions about how far and in what ways students' metahistorical understanding affects the kind of framework available to them, and about the extent to which any kind of recognizably historical past figures in orientation to the present and future. If research is to make progress in understanding historical consciousness it will need more sophisticated conceptual tools as well as empirical work; I'm going to call it ... 'Walking backwards into tomorrow'. I think it's less of a UK specific thing, more a comment on how, going into the future you can't obviously see what's ahead of you, because in my analogy you're walking the wrong way; you can only see what you've been through, and try to interpret that as the way the path is leading, that you're going to. You can see bits of what's at either side of you, so you can see fragmented bits of what's going on now, but you've got nearly the whole picture of what's gone before, but tomorrow will maybe still be a bit of a mystery, but at least we have the freedom to walk into tomorrow... Andrew, year 13